School Management Strategies for Improving Teacher Performance Through Clinical Supervision - Rafiqie, Musyaffa (Journal of Educational Management Research, 2025)
Clinical supervision is a professional support process provided to teachers to address instructional challenges through systematic steps involving lesson planning, observation of teaching behavior, and subsequent analysis and follow-up. This study employed a School Action Research method, collecting data through observation, field notes, and documentation. The research examined the principal’s efforts to improve teacher performance through clinical supervision. Findings revealed a steady and significant improvement in teacher performance, with scores increasing from 58.2% prior to intervention to 70.1% after the first cycle, and further rising to 83.7% after the second cycle. These results demonstrate that clinical supervision not only enhances teacher competence but also contributes to improved student learning outcomes. The observed improvements stemmed from more thorough lesson planning, effective classroom delivery, and better utilization of learning resources. This study reaffirms clinical supervision as an effective professional development strategy, capable of fostering continuous improvement in teaching quality and creating optimal learning conditions for students.